Bending, Curling, Rolling, and Salient Behavior of Molecular Crystals Driven by [2+2] Cycloaddition of a Styrylbenzoxazole Derivative. Issue 32 (5th July 2017) - Wang, Haoran; Chen, Peng; Wu, Zhu; Zhao, Jinyu; Sun, Jingbo; Lu, Ran
Abstract: We report interesting photomechanical behaviors of the dynamic molecular crystals of ( E )‐2‐(2, 4‐dichlorostyryl)benzo[d]oxazole (BOACl24 ). The photosalient effect of the rod‐like crystal based on a metal‐free olefin driven by photodimerization is observed. Moreover, the needle‐like crystals ofBOACl24 exhibit a reversible bending away from a UV light source. The nanofibers curl easily under UV irradiation in an organogel, in which the photo‐induced rolling of a small slice occurs. This suggests that the rapid release of the accumulated strain during photodimerization may lead to a photosalient effect, and the bending or curling happens when the strain is released slowly. Notably, [2+2] cycloaddition takes place between two different conformational isomers ofBOACl24 on account of the rotation of the benzoxazole ring around the C−C bond in an excited state before photodimerization. Such topo‐photochemical reaction has not been reported elsewhere. Abstract : Rollin' and tumblin' : The dynamic molecular crystals of (dichlorostyryl)benzoxazole BOACl24 exhibit photomechanical motion induced by topo‐photochemical dimerization. The reversible controllable bending of these needle‐like crystals away from the light source driven by [2+2] cycloaddition resulted from the slow release of the strain accumulated by the movement of the atoms during photodimerization.